Britain after empire : constructing a post-war political-cultural project / P.W. Preston. - Preston, P. W. (Peter Wallace), 1949- (Palgrave Macmillan, 2014)
Through compelling analysis of popular culture, high culture and elite designs in the years following the end of the Second World War, this book explores how Britain and its people have come to terms with the loss of prestige stemming from the decline of the British Empire.